Experimental investigation of micro EDM drilling in the CFRP using response surface methodology - Kaushik, Nitish; Jha, Sanjay Kumar; Anand, Ravi Shankar (Frontiers in Materials, 2023)
Recently, most of the conventional (industrial) materials such as steel, aluminum, and copper are being replaced by composite materials. Among the various composite materials, CFRP material is one of the most popular materials in many industries due to its excellent mechanical properties likehigh strength, high modulus, compressive strength, etc. However, the micro hole in mMicro EDM drilling in the CFRP composite material is challenging due to fiber orientation, uneven distribution of conducting fiber, and delamination affecting the material removal rate (MRR) and micro hole quality performance. The objective of the article is to optimize the process parameters for optimum hole quality in the micro EDM drilling of CFRP composites. For this purpose, response surface methodology is applied to investigate the effect of the input process parameters which are voltage, capacitance, and tool rotation speed on MRR, roundness error, and tapper of the micro-hole. produced by micro EDM. The experiments have been conducted according to the box behnken design of experiments. Regression equations, and response surfaces are developed. Optimum responses are determined by the desirability function approach. The experimental investigation shows that capacitance is the highly significant factor among the input process parameters affecting hole quality output responses such as MRR, roundness error, and tapper. The MRR increases with increasing the capacitance and tool rotation speed initially but its value decreases on further increasing the capacitance at a particular voltage. Roundness error and the tapper initially decrease on increasing capacitance and tool rotation speed then increases. The optimum MRR and hole quality are obtained in a range of 150 to 250 nF capacitance, and 1400 to 1600 rpm tool rotation speed, at 100 voltage.